PENGOLAHAN SAMPAH ORGANIK DAN ANORGANIK SEBAGAI IMPLEMENTASI P5 TEMA GAYA HIDUP BERKELANJUTAN PADA SISWA SMPIT AL-FIKRI MAKASSAR - Effendi, Nurmaya; Amin, Asni; Nontji, Maimuna; Putra, Muhammad Alfinur; Pertiwi, Ermy; Alnamira, Rezki (LPPM Universitas Bina Bangsa, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a cross-disciplinary learning to observe and think of the problem solutions in the surrounding environment using a project-based learning approach. This community service aims to improve the character building and competency of SMPIT Al-Fikri students in implementing the P5 in sustainable lifestyle theme in terms of processing organic and inorganic wastes into valuable products. The products of organic waste processing include eco-enzymes, bar soap- and handwash-based eco-enzymes; inorganic waste processing products were ecobrics; and aromatherapy candles as products of used-cooking oil processing. As our partners, 132 students of SMPIT Al-Fikri, Makassar, attended this community service activity The method of this community service includes preparation and socialization; education and counseling in organic and inorganic waste processing; training and mentoring in making eco-enzymes, bar soap- and handwash-based eco-enzymes, ecobrics, and aromatherapy candles; activity evaluation through pre-posttest questionnaires. Our partners in this community service showed enthusiasm during discussions and practices, which are then able to improve their knowledge, attitudes, and skills in processing organic and inorganic wastes. Furthermore, we hope that our partners can apply their knowledge and skills in everyday life to to reduce environmental pollution and improve their quality of life